Contracultura : Alternative Arts and Social Transformation in Authoritarian Brazil - Dunn, Christopher, 1964- (Book collections on Project MUSE., 2016)
" ... Exposes the inventive cultural production and intense social transformations that emerged during the rule of an iron-fisted military regime during the sixties and seventies. The Brazilian contracultura was a complex and multifaceted phenomenon that developed alongside the ascent of hardline forces within the regime in the late 1960s. Focusing on urban, middle-class Brazilians often inspired by the international counterculture that flourished in the United States and parts of western Europe, Dunn shows how new understandings of race, gender, sexuality, and citizenship erupted under even the most oppressive political conditions"--